Prognostic impact of lung adenocarcinoma second predominant pattern from a large European database. Issue 2 (10th November 2020) - Bertoglio, Pietro; Querzoli, Giulia; Ventura, Luigi; Aprile, Vittorio; Cattoni, Maria A.; Nachira, Dania; Lococo, Filippo; Rodriguez Perez, Maria; Guerrera, Francesco; Minervini, Fabrizio; Gnetti, Letizia; Bacchin, Diana; et al.
Abstract: Background and Objectives: Adenocarcinoma patterns could be grouped based on clinical behaviors: low‐ (lepidic), intermediate‐ (papillary or acinar), and high‐grade (micropapillary and solid). We analyzed the impact of the second predominant pattern (SPP) on disease‐free survival (DFS). Methods: We retrospectively collected data of surgically resected stage I and II adenocarcinoma. Selection criteria: anatomical resection with lymphadenectomy and pathological N0. Pure adenocarcinomas and mucinous subtypes were excluded. Recurrence rate and factors affecting DFS were analyzed according to the SPP focusing on intermediate‐grade predominant pattern adenocarcinomas. Results: Among 270 patients, 55% were male. The mean age was 68.3 years. SPP pattern appeared as follows: lepidic 43.0%, papillary 23.0%, solid 14.4%, acinar 11.9%, and micropapillary 7.8%. The recurrence rate was 21.5% and 5‐year DFS was 71.1%. No difference in DFS was found according to SPP ( p = .522). In patients with high‐grade SPP, the percentage of SPP, age, and tumor size significantly influenced DFS ( p = .016). In patients with lepidic SPP, size, male gender, and lymph‐node sampling ( p = .005; p = .014; p = .038, respectively) significantly influenced DFS. Conclusions: The impact of SPP on DFS is not homogeneous in a subset of patients with the intermediate‐grade predominant patterns. The influence of high‐grade SPP on DFS is related to its proportion in the tumor.